2021
DOI: 10.1039/d0fo02831b
|View full text |Cite
|
Sign up to set email alerts
|

Selenite supplementation modulates the hepatic metabolic sensors AMPK and SIRT1 in binge drinking exposed adolescent rats by avoiding oxidative stress

Abstract: Oxidative metabolism of ethanol after exposure to BD in hepatocytes, and its relationship with SIRT1 and AMPK through EROS and NADH/NAD+. Effects of selenium supplementation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…A study has confirmed that BD alters insulin production, causing IR, inhibiting glucose transport and decreasing exposure to it, making an increase in insulin secretion necessary (Shelmet et al., 1988). Recently, in male adolescent rats exposed to the same experimental intermittent BD protocol as that used in the present study, a downregulation of IRS‐1 in the liver and skeletal muscle was described (Nogales et al., 2021; Romero‐Herrera et al., 2023). Therefore, during adolescence in rats, insulin does not actively reach these tissues and, consequently, its physiological action decreases.…”
Section: Discussionmentioning
confidence: 51%
See 3 more Smart Citations
“…A study has confirmed that BD alters insulin production, causing IR, inhibiting glucose transport and decreasing exposure to it, making an increase in insulin secretion necessary (Shelmet et al., 1988). Recently, in male adolescent rats exposed to the same experimental intermittent BD protocol as that used in the present study, a downregulation of IRS‐1 in the liver and skeletal muscle was described (Nogales et al., 2021; Romero‐Herrera et al., 2023). Therefore, during adolescence in rats, insulin does not actively reach these tissues and, consequently, its physiological action decreases.…”
Section: Discussionmentioning
confidence: 51%
“…BD exposure during adolescence in rats leads to a dangerous profile of catabolic AMPK and SIRT‐1 expression in WAT, which together with their anabolic profile found in the liver of BD adolescent rats (Nogales et al., 2021), triggers the AT–liver axis, exacerbating WAT lipolysis and increasing the amount of circulating FFA. All of this could contribute to liver steatosis accompanied by an IR process, comprising a clear risk factor for the development of future cardiovascular diseases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The downregulation of sirtuins was observed in peripheral blood mononuclear cells in CVD patients with Se deficiency [ 19 ]. Recently, increased liver expression of SIRT1 was reported in binge drinking rats when supplemented with Se [ 25 ]. Knowledge on the effect of coenzyme Q 10 on SIRT1 is also limited, although the Q 10 status seems to influence SIRT1 activity [ 26 ], as the decline in hepatic SIRT1 expression in diabetic rats was reversed by coenzyme Q 10 administration [ 27 ].…”
Section: Introductionmentioning
confidence: 99%